ANALYSIS OF THE IMPLEMENTATION OF NURSING PROFESSIONAL VALUES IN REFERRAL HOSPITALS JAKARTA: FISHBONE ANALYSIS: DOI: https://doi.org/10.35654/ijnhs.v2i1.73 - Rutmauli Hutagaol (Alta Dharma Publisher, 2019)
Professional values ??can direct nurse behavior. Nurse behavior should reflect caring in providing nursing services as the essence of nursing. The method used in this paper is a case study. Data collection is done by interviews, document observation, and distributing questionnaires to nurses in the amount of 517 nurses. The questionnaire used was the Nursing Professional Value Scale and Nurse that was modified and used to determine the nurse's professional score scale. Interviews were conducted with the field and nursing committee using a semi-structured interview guide. Interview material includes management functions related to the application of the nurse's professional values. Data analysis using fishbone analysis. The results showed that the professional score scale of nurses was quite strong, namely 101.19, but the application of professional nurses' values ??was still not optimal because some nursing leaders were still less professional. The recommendation from this case study is that nursing management needs to motivate nurses to apply nurses' professional values ??through attitudes and behaviors that have implications for the quality of nursing services and have an impact on patient satisfaction and safety.